THE RELATIONSHIP BETWEEN THE HOUSEHOLD WASTEWATER DISPOSAL SYSTEM AND THE QUALITY OF WELL WATER IN THE PURI ANGSA ASRI 2 HOUSING AREAS IN MUARO JAMBI - Eliza, Loli; Zuli Rodhiyah; Winny Laura Christina Hutagalung (Lingkar: Journal of Environmental Engineering, 2025)
Water is a basic human need that is used for various household purposes, so the availability of clean water that is safe and suitable for consumption has a great effect on public health. In Puri Angsa Asri 2 Muaro Jambi Housing, the community uses dug well water as the main source of clean water, but the quality of dug well water is greatly influenced by the household wastewater disposal system. Non-standard sewage disposal systems, such as direct discharge into the ground or open channels without treatment, have the potential to cause groundwater pollution. This study aims to analyze the relationship between the household wastewater disposal system and the water quality of dug wells. The research was conducted with a quantitative approach through the analysis of Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), turbidity, and coliform parameters, and tested using Chi-Square with Fisher's Exact Test. The results show that most wastewater disposal systems do not meet the standards of the Indonesian Minister of Health Regulation No. 2 of 2023 concerning Environmental Health Requirements to be pollutant-free. Most of the samples also did not meet the quality standards of the Minister of Health Regulation No. 2 of 2023 concerning water for hygiene and sanitation purposes and Government Regulation No. 22 of 2021 for class I water. Statistical analysis showed BOD values (p=0.067), COD (p=0.300), turbidity (p=0.183), and coliform (p=0.183). Although the statistical relationship is not significant, there are indications that non-standard wastewater treatment systems contribute to increased organic and microbiological contamination of dug well water.